2022
DOI: 10.1002/ps.7073
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of macadamia felted coccid (Hemiptera: Eriococcidae) damage and cultivar susceptibility using imagery from a small unmanned aerial vehicle (sUAV), combined with ground truthing

Abstract: BACKGROUND Macadamia felted coccid, Acanthococcus ioronsidei (Williams) (Hemiptera: Eriococcidae), is a significant pest of macadamia nut, Macadamia integrifolia Maiden & Betche (Protaceae), in Hawaii, and heavy infestations can kill branches, resulting in characteristic dead, copper‐colored leaves. Small Unmanned Aerial Vehicles (sUAV) or ‘drones,’ combined with spatial data analysis, can provide growers with accurate and high‐resolution detection of plant stress due to pest infestations. We investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Traps were replaced every month, and numbers of parasitoids and predators stuck on traps were microscopically tallied as means ± SEM of parasitoids and five species of coccinellids/trap/month/orchard during twelve months of 2015. Encarsia lounsburyi (Berlese & Paoli) (Hymenoptera: Aphelinidae), a parasitoid of male MFC, and Curinus coeruleus Mulsant (Coleoptera: Coccinellidae) were the dominant parasitoid and ladybeetle in macadamia fields, respectively, during this survey [12].…”
Section: Extant Natural Enemies In Hawaiimentioning
confidence: 83%
See 1 more Smart Citation
“…Traps were replaced every month, and numbers of parasitoids and predators stuck on traps were microscopically tallied as means ± SEM of parasitoids and five species of coccinellids/trap/month/orchard during twelve months of 2015. Encarsia lounsburyi (Berlese & Paoli) (Hymenoptera: Aphelinidae), a parasitoid of male MFC, and Curinus coeruleus Mulsant (Coleoptera: Coccinellidae) were the dominant parasitoid and ladybeetle in macadamia fields, respectively, during this survey [12].…”
Section: Extant Natural Enemies In Hawaiimentioning
confidence: 83%
“…In 2014, estimates on one farm indicated that as much as half a million pounds of wet in-shell macadamia nuts were lost because of MFC. According to USDA National Agricultural Statistics Service, the highest quantity of macadamia nuts, i.e., 6879.6 hectares, is harvested in Hawaii, and the farm value for the 2017-2018 crop was estimated at USD 53.9 million [4,12,13].…”
Section: Introductionmentioning
confidence: 99%